IMPLEMENTASI NILAI-NILAI PANCASILA MELALUI PEMBELAJARAN PKN DI SEKOLAH DASAR (STUDI KASUS DI SD NEGERI 134409 KOTA TANJUNGBALAI) - Nurhasanah; Oktavy, Mita; Krisman Zega, Darling; Azhari, Saadah; Dharma, Surya; Yunita, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of Pancasila values through Civic Education (PKn) learning in elementary school. The research was conducted at SD Negeri 134409 Tanjungbalai City in Grade V, Semester 2, with teachers and students as subjects. Data were collected through direct observation using a structured observation sheet containing 20 behavioral indicators divided into five aspects corresponding to the five principles of Pancasila. Results showed that implementation of Pancasila values through PKn learning was carried out very well, evidenced by a total score of 92 out of 100 (92%). The First Principle (Belief in One God) and the Fifth Principle (Social Justice) achieved perfect scores of 100%, while the Second and Fourth Principles each scored 85%, and the Third Principle scored 90%. All eight planned teaching strategies were implemented by the teacher. Supporting factors include teacher modeling, habituation of prayer, and the use of varied teaching methods. Obstacles include students who were less disciplined in discussions, uneven participation in group work, and low awareness of loving local products.